“E-Public Sociology” as a Critical Sociological Intervention - Nicklich, Manuel; Sauer, Stefan (Momentum Quarterly, 2021)
In comparison with business administration, economy and recently virology, sociology plays a rather subordinate role in public discourse. According to this, two paradoxes unfold: (a) in the discussion of societal problems sociology seems irrelevant although the discipline can be seen as predestined in dealing with those issues and (b) if it is involved it is assigned a special rather peripheral role. In the debate about public sociology increasingly the concept of “E-Public Sociology” emerges and emphasizes the almost unconditional communication with an interested public. In our text we develop a two-by-two scheme to analyze sociological effects in public and corresponding concept of communication with a special focus on podcasts as a part of “E-Public Sociology”. With a focus on podcasts as special form of sociological activity between public sociology and sociology in public, we exemplify the new possibilities induced by digital transformations and evaluate how sociological podcasts might be seen as legitimate societal intervention. We show that it is not enough to simply increase visibility of the discipline, but you need a more systematic approach.
Keywords: public sociology; critical theory; podcasts; sociological diagnosis